Turbulent periodic flow and heat transfer in a rectangular channel with detached V-baffles - Kaewkohkiat, Y.; Promvonge, P.; Eiamsa-ard, S. (My University, 2017)
This paper presents a numerical analysis of turbulent periodic flow and heat transfer in a rectangular channel with detached V-baffles. The computations are based on the finite volume method with the SIMPLE algorithm for handling the pressure–velocity coupling and using the QUICK scheme for the convection terms. Air is used as the test fluid with the air flow rate in terms of Reynolds numbers ranging from 3000 to 20,000. The effects of different detached-clearance ratios (c/H, CR) of 0.0, 0.05, 0.1, 0.15, and 0.2, baffles-pitch to square channel-diameter ratio (pitch ratio (p/H), PR) is 1.0, baffles-height to square channel-diameter ratio (blockage ratio (b/H), BR) is 0.10, and attack angle (α) is 45◦ on heat transfer, friction factor and thermal enhancement factor are investigated numerically. It is found that a pair of counter-rotating vortices (P-vortex) caused by the baffles can induce impingement/attachment flows repeatedly on the rectangular channel walls leading to a greater increase in the heat transfer over the test channel. The maximum thermal performance and heat transfer are found to be about 1.5 and 3.3, respectively for CR = 0.05 and Re = 3000, while the highest pressure loss is about 21.5 in the case of CR = 0.2 and Re = 20,000.